KONSEP KAJIAN ORIENTALIS TERHADAP HADIS (Jurnal Studi Alquran dan Hadis) - A.A. ARTOY, SITI ZAHRA (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2023)
The study of the eastern world has become a self-attraction of the orientalists. It is not surprising that the Qur’an and the Hadith do not escape their criticism. Therefore, a critical thought was born about the study of the author used the library study as a method in complication and obtained a result that the desire of the orientalists to study the world of the hadith rather than to spread an unreasonable opinion of the Islamic religion, but became a desire obsession with the religion of Islam, one of them btw of researching the authoritative a hadith. with the supporting factors of their studies there are two things. First, their study of the hadith focused on the Matan, and was helped by the involvement of their thinking with the aspects of Methodology, Sosio Graphic Kutral, word view as well as language. Second, from the thinking carried out was born the theory and methods of the orientalist that the criticism of Matan is the result of the thinking of Ignaz Goldziher, as The main pioneer in the study of critical hadith. Then projecting back and Argument E-Silentio Which is the result of the thinking of Joseph Schacht, Common Link is a theory developed from Schacht’s thinking by G.HA. Jyunboll, Dating and Isnad Matan Analiysis by Harlad Motzki and Explosive Isnad and the Isnad Family Nabia Abbot.